CONTRATO E CONDIÇÕES DE TRABALHO DOS CATADORES DE MATERIAIS RECICLÁVEIS: o caso do Maranhão a partir dos anos 2000. - ALMEIDA, Rosângela Batista (2018)
With the advancement of the productive forces many of the workers do not fall more in the market, causing the work, which is the source of wealth and support of society and also, principal booster of capitalist reproduction was being weakened and this caused many Seek alternative means to ensure their livelihood. In this way, these activities performed by much of the population that had great advancement from the 1970 were known for informal activities, and due to this situation and increasing enlargement of this activity, this form of work marks the current phase of the Global capitalism, where workers are incorporated into production being informally exploited, performing jobs through associations and cooperatives or even selling their workforce informally. At the moment, the work is measured by the production of the worker, blaming them for their work these are overexploited, and still has no guarantee, because they are deprived of labor rights. The system to perpetuate its reproduction transforms the means of production and creates forms of exploitation that reduce the cost of production, in addition to diminish the time of use of the goods enabling profitability and boosting exacerbated consumption, causing the increase Of the production of solid waste grow enormously so that the phenomenon of recycling is defended as action focused on the conservation of the environment and not as reproduction of the capitalist accumulation, because the recyclables reach industries through the work of the scavengers of Recyclable materials, direct subjects of the work precarious. In this research we analyze the reflections of these various transformations in the world of work, seeking to unravel the nexus that involve the relationship between "informality" and capitalism. This was done from a case study on a segment of workers, more precisely, recyclable waste pickers in the state of Maranhão.